Predictors of internalised HIV-related stigma: a systematic review of studies in sub-Saharan Africa - Pantelic, M.; Shenderovich, Y.; Cluver, L.; Boyes, Mark (Routledge, 2015)
This systematic review aims to synthesise evidence on predictors of internalised HIV stigma amongst people living with HIV in sub-Saharan Africa. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used. Studies were identified through electronic databases, grey literature, reference harvesting and contacts with key researchers. Quality of findings was assessed through an adapted version of the Cambridge Quality Checklists. A total of 590 potentially relevant titles were identified. Seventeen peer-reviewed articles and one draft book chapter were included. Studies investigated socio-demographic, HIV-related, intra-personal and interpersonal correlates of internalised stigma. Eleven articles used cross-sectional data, six articles used prospective cohort data and one used both prospective cohort and cross-sectional data to assess correlates of internalised stigma. Poor HIV-related health weakly predicted increases in internalised HIV stigma in three longitudinal studies. Lower depression scores and improvements in overall mental health predicted reductions in internalised HIV stigma in two longitudinal studies, with moderate and weak effects, respectively. No other consistent predictors were found. Studies utilising analysis of change and accounting for confounding factors are necessary to guide policy and programming but are scarce. High-risk populations, other stigma markers that might layer upon internalised stigma, and structural drivers of internalised stigma need to be examined.